2022
DOI: 10.1136/ijgc-2022-003404
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and gynecological cancer outcomes: opportunities to improve quality of life and survival

Abstract: Sleep is important for immune function, metabolic function and physical repair. Sleep is more commonly disrupted in women compared with men and is disrupted by surgery, chemotherapy, and cancer itself, making gynecological oncology patients at higher risk of insomnia and sleep disruption. Insomnia and sleep disruption are linked to increased pain, poorer quality of life, depression, and anxiety which can all negatively affect patient outcomes. A number of environmental, behavioral, and pharmacological interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…IL-6, TNF-α, and IL-1β are proinflammatory cytokines [28]. Prior research has found that TNF-α is essential for the sleep-wake cycle, and both elevations and decrements can disrupt the homeostasis necessary for efficient sleep [11,29]. These results suggest that greater inflammation is associated with less light physical activity, more sedentary behavior, and less efficient sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6, TNF-α, and IL-1β are proinflammatory cytokines [28]. Prior research has found that TNF-α is essential for the sleep-wake cycle, and both elevations and decrements can disrupt the homeostasis necessary for efficient sleep [11,29]. These results suggest that greater inflammation is associated with less light physical activity, more sedentary behavior, and less efficient sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Each blood sample was evaluated for the presence of circulating markers of inflammation, which included interleukin 10 (IL-10), interleukin 1β (IL-1β), tumor necrosis factor α (TNFα), interleukin 6 (IL-6), interleukin 1 receptor antagonist (IL-1Ra), tumor necrosis factor receptor 1 (TNFR1), tumor necrosis factor receptor 2 (TNFR2), and c-reactive protein (CRP). These inflammatory biomarkers were selected because previous studies have shown that they are associated with physical activity and sleep, they are relatively stable over time, and they are readily detectable using existing laboratory methodologies [10,11,13]. All blood samples were sent to the Cancer Control and Psychoneuroimmunology Lab at the University of Rochester for analysis.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when sleep appears abnormal, it should be actively intervened. Previous studies have shown that sleep can be improved before, during, and after cancer treatment through certain interventions, such as cognitive behavioral therapy, a regular sleep schedule, limit caffeine intake, exercise therapy, ambient noise limitation, melatonin and other medications [ 40 ]. Second, our investigation had a prospective design, characterized by high baseline survey participation rate and follow-up retention rate, which could reduce the potential for recall bias and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…35 Lack of sleep is also linked to inadequate pain management, depression, and overall QoL scores among women with cancer. Zhao and colleagues 36 provide supporting evidence and strategies for sleep optimization in women with gynecologic cancers. The ACLM website (www.lifestylemedicine.org) provides patient education material to address sleep disruptors and proposes evidence-based strategies to improve sleep hygiene.…”
Section: Sleep and Stressmentioning
confidence: 95%